2018
DOI: 10.3892/mmr.2018.9095
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate biomarkers and pathways associated with SCLC by bioinformatics analysis

Abstract: Small cell lung cancer (SCLC) is one of the highly malignant tumors and a serious threat to human health. The aim of the present study was to explore the underlying molecular mechanisms of SCLC. mRNA microarray datasets GSE6044 and GSE11969 were downloaded from Gene Expression Omnibus database, and the differentially expressed genes (DEGs) between normal lung and SCLC samples were screened using GEO2R tool. Functional and pathway enrichment analyses were performed for common DEGs using the DAVID database, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…For example, TOP2A is one of genes with the most nodes, and it is a subfamily of DNA topoisomerase II, which controls and changes the topological state of DNA during transcription. A previous study has shown that TOP2A is overexpressed in SCLC (34). The lower the differentiation degree of tumors, the higher the expression level of TOP2A (35).…”
Section: Discussionmentioning
confidence: 95%
“…For example, TOP2A is one of genes with the most nodes, and it is a subfamily of DNA topoisomerase II, which controls and changes the topological state of DNA during transcription. A previous study has shown that TOP2A is overexpressed in SCLC (34). The lower the differentiation degree of tumors, the higher the expression level of TOP2A (35).…”
Section: Discussionmentioning
confidence: 95%
“…To correlate the levels of NF-YA expression to proliferation of lung tumor cells, the 501 TCGA tumors were binned according 10 different NF-YA expression levels, from high to low (Figure 3, upper panel). Thereafter, we measured expression of five genes commonly considered as proliferative markers, Ki67, TOPO IIa, BUB1, CENP2, FOXM1, including in lung cancers [36,37,38,39]; in the 10 NF-YA cohorts, all showed progressively decreasing levels from high-to-low NF-YA expressing tumors (Figure 3). The calculated statistical significance for each gene is high ( p values 10 −10/16 ).…”
Section: Resultsmentioning
confidence: 99%
“…STRING analysis also indicated that MCM2-7 had a significant correlation with MCMBP, GINS3, GINS2, GINS1, POLA2, CDC7, DBF4, PRIM1, CDC6, ORC3, LRWD1, ORC4, ORC5, CDC45, TIPIN, POLE2, RFC3, ORC6, ORC2, ORC1, GMNN, CCNA2, CDT1, MCM8, MCM10, POLA1, RPA2, RFC4, TIMELESS, RAD52, RPA1, RPA3, GINS4, CDK2, CLSPN, CHEK1, BLM, WRN, RMI1, and TOP3A, which forms an important network to perform a series of pathophysiological functions at the protein level. Wen et al constructed a network in association with small cell lung cancer by bioinformatics analysis, indicating that the interactions among MCM2/3/6 and other hub protein were involved in carcinogenesis [ 67 ].…”
Section: Discussionmentioning
confidence: 99%